Deep Donkey and Dadirri: asking Creatura out to play - Duncan, Roger (Murmurations: Journal of Transformative Systemic Practice, 2021)
This article is based on the premise that we are currently awakening to the full systemic impact of the emerging global ecological crisis which is already having a devastating effect on the ecosystems of the earth and also a highly destructive impact on psychological well-being. The ecological crisis has coincided with the painful awakening to the social and environmental destruction that has resulted from the legacy of a colonial world view of nature and culture. These events now demand a radical and deep adaption of our view of nature and culture. It is becoming clear that we are facing not only an ecological break down and a narrative collapse, but also a breakdown in how to make sense of what we are facing. This article explores how systemic psychotherapy and Gregory Bateson’s work on the gnostic ideas of pleroma and creatura, can provide a framework to support the Decolonial Turn but also an EcoSystemic Return. This article uses the children’s game of Donkey and the Indigenous Australian practice of Dadirri to playfully explore how we might overcome Bateson’s notion of epistemological error when engaging with systemic practice, Indigenous nature practice and quantum physics. The article suggests an imaginary game of Deep Donkey to overcome the destructive legacy of Cartesian dualism at the core of western culture and to begin to open western imagination to an intra-subjective dialogue with nature. I suggest the game of Deep Donkey could a helpful practice in realigning western thinking with sophisticated and long subjugated Indigenous ecological and cultural wisdom.